2020
DOI: 10.3389/fvets.2020.00180
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography to Assess Thermoregulatory Reactions of Female Buffaloes in a Humid Tropical Environment

Abstract: This study employed infrared thermography to assess the thermoregulatory responses of female buffaloes reared in a hot and humid climate as a function of variations in time and the thermal environment, and to correlate rectal temperature with that of different body areas. The trial was carried out at Embrapa Eastern Amazon (01 • 26'S and 48 • 24'W) in Belém, PA, Brazil. Twenty-four female buffaloes fed exclusively on pasture and exposed to the sun throughout the day in an open area were used. The animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…According to Barros et al (11), orbital area maximum temperature has the highest correlation with buffalo and cattle rectal temperature, being the most appropriate area to evaluate the animal's thermal conditions, since it suffers interference from the ambient temperature. In addition, Brcko et al (32) used thermography in several areas of buffalos and verified that eye and cheek could determine thermal stress because these areas are best correlated with the animal's RT. VUL region and tail insertion also appeared to be promising body regions; however, the practical application is questionable because of invasive management for tail occlusion (13).…”
Section: Discussionmentioning
confidence: 99%
“…According to Barros et al (11), orbital area maximum temperature has the highest correlation with buffalo and cattle rectal temperature, being the most appropriate area to evaluate the animal's thermal conditions, since it suffers interference from the ambient temperature. In addition, Brcko et al (32) used thermography in several areas of buffalos and verified that eye and cheek could determine thermal stress because these areas are best correlated with the animal's RT. VUL region and tail insertion also appeared to be promising body regions; however, the practical application is questionable because of invasive management for tail occlusion (13).…”
Section: Discussionmentioning
confidence: 99%
“…Increased RR and pulse rate (PR) reflected the response of animals, as an adaptive strategy, to lower down their body temperatures through evaporative cooling. Studies have reported higher RR and RT but lower PR in buffaloes exposed to high temperatures in a climatic chamber (3) and under pasture grazing system (20). Similarly, dramatic increases in RR, RT, and PR have been observed in cattle under heat stress conditions (21).…”
Section: Effect Of Thi On Physiological Parametersmentioning
confidence: 95%
“…A study in bovines gender Bos, demonstrated that temperatures measured on the forehead mirrored rectal temperature better than readings taken on the flank, udder, rump, ears or cheek (Peng et al 2019). In female buffaloes -at least those raised in tropical humid environs-ocular and cheek temperatures correlate most positively and significantly with rectal temperature (Brcko et al 2020).…”
Section: Thermal Windows In the River Buffalomentioning
confidence: 98%